Physiological Impacts, Regulations, and Ethical Implications of Doping in Sports: A Systematic Literature Review - Nimrot Manalu; Fahri Ridwan; Sopater Ndruru (Joska: Jurnal Isori Kampar, 2026)
Objectives: This systematic literature review aims to analyze the physiological impacts of doping substances in sports, examine current regulatory frameworks, and evaluate ethical implications for competitive integrity. The study synthesizes existing research to provide a comprehensive understanding of doping's multifaceted effects on athletic performance and sports governance. Methods: A systematic literature review was conducted using electronic databases including PubMed, Scopus, Web of Science, and SportDiscus from January 2010 to December 2024. Search terms included "doping," "performance-enhancing drugs," "anti-doping regulations," "sports ethics," and "physiological effects." Studies were selected based on predefined inclusion criteria focusing on peer-reviewed articles examining doping impacts, regulatory effectiveness, and ethical considerations in competitive sports. Results: A total of 127 studies met the inclusion criteria and were analyzed. Results revealed significant physiological impacts of various doping substances on cardiovascular, muscular, and endocrine systems. Current anti-doping regulations show varying effectiveness across different sports and regions. Ethical implications demonstrate substantial negative effects on fair play, athlete health, and competitive integrity. Emerging challenges include designer drugs, biological doping, and technological advancement in detection methods. Conclusion: Doping represents a complex multidisciplinary challenge requiring integrated approaches combining scientific research, regulatory enforcement, educational initiatives, and ethical frameworks. Current anti-doping efforts show progress but require continuous adaptation to address evolving doping practices. Enhanced international cooperation and comprehensive athlete education programs are essential for maintaining competitive integrity.